A state-of-the-art toolkit for document clustering - Greene, Derek (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2007)
Cluster analysis refers to a family of procedures which are fundamentally concerned with automatically arranging data into meaningful groups. These procedures are increasingly being employed in knowledge discovery tasks to assist in the exploration and interpretation of large datasets. Since users may often be unfamiliar with the exact contents of a dataset, clustering can provide a means of introducing some form of organisation to the data, which can also serve to highlight significant patterns and trends.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin